From individual to community : issues in development studies : essays in memory of Malcolm Adiseshiah - Saleth, R. Maria 1955-; Adiseshiah, Malcolm S.; Madras Institute of Development Studies (New Delhi SAGE Publications, 2012)
Malcolm S. Adiseshiah, Indian development economist; contributed articles.
Includes bibliographical references and index
Keywords: Economic development -- Social aspects -- India; Rural development -- India; Political sociology